Comparison of demographic features and prognosis between cardiogenic shock in patients with Chagas heart disease and other etiologies – Registry Of Acute Medical Emergencies in Brazil (ROAD). (25th November 2020) - Pessoa, R.S; Rizerio, B.G; Biselli, B; Silva, P.G.M.B; Roque, E.C; Furlan, V; Araujo, V.A; Wetten, M.P; Cesar, M.C; Teixeira, R.L; Balbao, H.B.B; Lopes, R; et al.
Abstract: Background: Chagas disease is a chronic, systemic, parasitic infection caused by Trypanosoma cruzi, and a common cause of heart failure (HF) in Latin America. The incidence can be as high as 14% in endemic areas. The prognosis seems to be worse than other causes of HF, with mortality of up to 20%/year. Mortality and prognosis during the acute decompensation, however, are less studied. Purpose: Compare differences between cardiogenic shock (CS) in patients with HF caused by chronic Chagas heart disease (ChHD) and those caused by other etiologies (non-ChHD). Methods: We performed a multicentric, prospective, observational study of patients admitted with CS at 3 emergency departments in Brazil between January 2015 and December 2019. Baseline characteristics and intrahospital outcomes were obtained. Statistical analysis: The primary outcome was combined intra-hospital events (death, stroke, acute renal failure and bleeding). Comparison between groups was performed through Chi-squared and Student's T-test and the multivariate analysis by logistic regression, being p<0.05 considered significant. Results: 856 patients with CS were included, 158 (18, 5%) ChHD and 698 (81, 5%) non-ChHD. Those with ChHD were younger (60.5±11.7 vs. 64.9±4.8 years old, p<0.0001), less often male (50.0 vs. 64.3%, p=0.001) and had lower prevalence of diabetes (20.9 vs. 36.2%, p<0.0001), hypertension (36.07 vs. 64.1%, p<0.0001), chronic obstructive pulmonary disease (1.9 vs. 7.8%, p=0.007) and dyslipidemia (14.6 vs. 36%, p<0.0001). The ejection fraction was lower in ChHD (26 + 7.3 vs. 30.4% + 11.4, p<0.0001) and they had more definitive pacemaker (17.3 vs. 6.8%, p<0.0001). At the admission, patients with ChHD had lower systolic blood pressure (91.3±20.6 vs. 98.8±25.9 mmHg, p=0.001) and were more symptomatic, with orthopnea (41.3 vs. 28.3%, p=0.004), dyspnea (75.3 vs. 57.3%, p<0.0001). Treatment in the first 24 hours was different, with less withdrawal of beta-blockers (51.2 vs. 63.9%, p=0.006) and more use dobutamine (80.4 vs. 66.2%, p<0.0001). Main cause of decompensation was progression of disease in 39.1% of ChHD versus 22.9% of non-ChHD (p<0.001). Decompensation seemed more severe with greater necessity of orotracheal intubation (30 vs. 14.5%, p<0.0001), intra-aortic balloon pump (27.9 vs. 7.5%, p<0.0001), bleeding (9.2 vs. 3.8%, p=0.012) and acute renal failure (46.7 vs. 35.8%, p=0.024). The primary outcome was observed in 57% of the non-ChHD and 71.5% of the ChHD (OR 0.578, 95% CI: 0.314–1.064, p=0.079). Also, there were no differences between intra-hospital mortality in patients with ChHD versus non-ChHD (37.3 vs. 32.7%, p=0.261). Conclusion: To the best of our knowledge, this is the biggest registry with Chagasic patients in cardiogenic shock. They were younger and had less comorbidities, but were admitted with lower blood pressure, more symptoms and needed more inotropes in the first 24 hours. No difference in mortality or combined outcome was observed. Funding Acknowledgement: Type of funding source: None